Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.